2015
DOI: 10.14716/ijtech.v6i3.1458
|View full text |Cite
|
Sign up to set email alerts
|

Visibility Analysis of Hospital Inpatient Ward

Abstract: The objective of this study is to evaluate the performance of hospital inpatient ward spatial configuration in relation to visibility. Visibility is an important aspect in a hospital inpatient ward, and could support healthcare performance. Visibility is required in an inpatient ward for the purposes of control, surveillance, interaction and communication among patients and nurses, and it could be affected by the spatial configuration of the ward. Based on isovist as a way to visualize the visual experience in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 2 publications
(5 reference statements)
1
20
0
Order By: Relevance
“…Pati and colleagues (2015) found that decentralized nursing design results in a decline in face-to-face interaction and collaborative communication. The central nurse station can be perceived as a critical place for patient supervision, interaction among staff, and surveillance of visitors (Johanes & Atmodiwirjo, 2015; Pati, Harvey, Redden, Summers, & Pati, 2015). The spatial relationship of the nurse station with patient rooms, and with other nurse stations, is emphasized (Johanes & Atmodiwirjo, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Pati and colleagues (2015) found that decentralized nursing design results in a decline in face-to-face interaction and collaborative communication. The central nurse station can be perceived as a critical place for patient supervision, interaction among staff, and surveillance of visitors (Johanes & Atmodiwirjo, 2015; Pati, Harvey, Redden, Summers, & Pati, 2015). The spatial relationship of the nurse station with patient rooms, and with other nurse stations, is emphasized (Johanes & Atmodiwirjo, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The configuration of units, 36 different qualities of seating arrangements 37 and physical design features (e.g. size, shape, lighting and furnishing of spaces) were among factors that influence face-to-face interactions in healthcare facilities.…”
Section: Introductionmentioning
confidence: 99%
“…This research uses a computational approach to analyse the spatial organisations of the lobby and outpatient area of Universitas Indonesia Hospital. A computational tool based on isovist and visibility graph in analysing the visibility properties of a spatial configuration has been developed in our previous study (Johanes & Atmodiwirjo, 2015). In the current study, the tool is extended to visualise the VCA of the signage to assist the wayfinding system optimisation.…”
Section: Visibility Analysis and Signage Design Workflowmentioning
confidence: 99%
“…Visibility analysis can be conducted systematically by using computational tools (Johanes & Atmodiwirjo, 2015;McElhinney & Psarra, 2014;Turner et al, 2001). The use of visibility analytical tools can provide valuable insight for examining and optimising the visibility properties of a spatial configuration.…”
Section: Introductionmentioning
confidence: 99%